ENTERPRISE INTERNET MARKETING: METHODS, TOOLS, DEVELOPMENT TASKS - SHARKO, Vitalii; TERNOVA, Alla; KRYVESHCHENKO, Viktoriya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The impact of globalization processes on the competitive business environment requires a modern understanding and the use of new approaches to meet the needs of the modern consumer. For a long period of time, all business entities, in particular the agricultural sector, have taken various measures to promote their products and services. Effective promotion of the products of the agrarian sector enterprise is able to ensure their stable position on the market, financial stability and competitiveness in the modern business environment. However, today’s realities have changed the form of promotion of goods and services, which was generally accepted, does not sufficiently reproduce the facts of increasing the efficiency of management and economic growth of business entities, but, on the contrary, testify to the need to change the paradigm of modern means of promoting goods and services on the market. Effective management of agrarian business in the conditions of informatization of the economy requires the use of innovative technologies and methods of promoting the product (raw material) and/or brand to the market. Internet marketing can be considered a necessary combination of innovative technologies and methods in marketing in modern economic conditions. It will contribute to the emergence of new innovative tools and methods for marketing activities, which help to more fully identify and satisfy the needs of consumers and, as a result, maximize the company’s profits The article discusses methods and tools of Internet marketing. The types of tools, components of traditional and non-traditional methods of Internet marketing are systematized. The reasons for the slow development of Internet marketing of enterprises in the agrarian sector have been studied. The main tasks of Internet marketing in the further activities of enterprises of the agrarian sector are determined according to the constituent elements proposed in this work.